(untitled) (International Journal of Architecture and Urbanism, 2022)
The population that continues to grow every time affects the total wastewater that is accommodated and channeled by drainage. This study aims to evaluate the existing condition of drainage dimensions on Tuamang Road, Medan. To determine whether the drainage can still channel the design wastewater discharge for the next 10, 20, and 30-year return periods or if it requires re-planning. The descriptive-evaluative method is used to evaluate drainage with stages starting from collecting data on population, annual rainfall, and measuring the dimensions of drainage channels; hydrological analysis, population projections for 10, 20, and 30-year; and evaluation of drainage channels. The research location is on Tuamang Road with a length of 1,200 m from Domestic House No. 130 to No. 101. The drainage system on Tuamang Road can still channel rainwater runoff and household waste for up to 10-year, based on analysis. 20 and 30-year, the dimensions must be enlarged to 1.0 m (bottom width) and 0.7 m (wet height of the channel). Cleaning sediment at the channel bottom must continue regularly to ensure the drainage system is working properly